Diagnosis and management of breast cancer in men. Issue 3 (May 2016) - Sellers, Laura; Miller, Rowan; Aggarwal, Ajay
Abstract : Male breast cancer accounts for less than 1% of all breast cancer cases. Compared with female breast cancer, it is associated with a worse overall survival, predominantly due to advanced stage at presentation. 1 The authors discuss the evidence to date regarding the epidemiology, clinical presentation and mode of diagnosis, as well as current treatment strategies.